2021
DOI: 10.3389/fpsyt.2021.706506
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Effect of Electroconvulsive Therapy on Obsessive-Compulsive Disorder Comorbid With Body Dysmorphic Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a chronic psychiatric condition that is associated with considerable morbidity, and ~90% of individuals with OCD have another psychiatric comorbidity. Patients with comorbid OCD and body dysmorphic disorder (BDD) have limited insight and poor psychosocial function, respond poorly to drug treatment, and have an increased risk of suicide. Modified electroconvulsive therapy (ECT) has been attempted to improve symptoms of OCD when drug treatment does not have a satisfactory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A recent report of a 50-year-old woman diagnosed with comorbid treatment-resistant major depressive disorder and body dysmorphic disorder found that electroconvulsive therapy, which has proven value in the treatment of medication-resistant depression, resolved and sustained remission of both conditions for 2 months [4]. Although these findings are initial and further research is required, they suggest that electroconvulsive therapy may be useful in managing more severe cases [4,12]. Other studies have found a potential effect of psychedelics in the treatment of primary features in BDD, but more data about safety and efficiency is necessary [10].…”
Section: Future Directionsmentioning
confidence: 97%
“…A recent report of a 50-year-old woman diagnosed with comorbid treatment-resistant major depressive disorder and body dysmorphic disorder found that electroconvulsive therapy, which has proven value in the treatment of medication-resistant depression, resolved and sustained remission of both conditions for 2 months [4]. Although these findings are initial and further research is required, they suggest that electroconvulsive therapy may be useful in managing more severe cases [4,12]. Other studies have found a potential effect of psychedelics in the treatment of primary features in BDD, but more data about safety and efficiency is necessary [10].…”
Section: Future Directionsmentioning
confidence: 97%
“…Compared to the general population, all-cause mortality is twice as high, and comorbid other psychiatric disorders can further increase the risk ( 3 ). Estimates suggest that up to 90% of individuals with OCD have a comorbid psychiatric disorder ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%